Analysis of Non-Financial Compensation in Improving Employee Work Motivation in the Hybrid Work Era - Ramaliyana Nur Maqfiroh; Gennie Yuliansyah; Ezra Jeremiah Kurniawan; Agung Zulfikri (ARMADA : Jurnal Penelitian Multidisiplin, 2026)
This study aims to analyze the role of non-financial compensation in enhancing employee motivation in the hybrid work era. Digital transformation and global shifts are driving companies to implement more flexible work models, which have implications for human resource management, particularly regarding employee motivation and performance.  In this context, non-financial compensation is becoming increasingly important as it can address employees’ psychological and social needs that cannot be met by financial rewards alone. This study employs a literature review method to analyze various relevant recent scientific journals. The findings indicate that non-financial compensation, such as recognition, a supportive work environment, career development opportunities, and work flexibility, has a positive and significant impact on employee motivation. Additionally, the implementation of a hybrid work system further underscores the importance of non-financial elements in enhancing employee engagement and satisfaction. However, challenges such as digital fatigue and a decline in social interaction still need to be managed effectively. Therefore, companies must balance financial and non-financial compensation appropriately to foster sustainable work motivation and improve employee performance in the hybrid work era.